PERBANDINGAN KONSEP PENDIDIKAN AKHLAK IBNU MISKAWAIH DAN IBNU SAHNUN - Sayfulloh, Usman Hamid; Dewi, Eva; Khalid, Muhammad Idkham (Universitas Al-Amien Prenduan, 2024)
Abstract: The aim of this research is to examine how the concept of moral education and Ibn Miskawaih and Ibnu Sahnun can be applied in this modern era which is full of moral decline. Using a qualitative descriptive method by utilizing literature review is a relevant method for this research using content analysis techniques, because it allows researchers to analyze moral concepts, classical values, and practice educational character through an in-depth understanding of various comparisons of Ibn's moral education concepts. Miskawaih and Ibn Sahnun. Ibn Miskawaih's concept of morals is a middle position, extreme advantages and extreme disadvantages, while Ibn Sahnun's concept of morals is to highlight morals. Teachers should teach etiquette to students, because it is an obligation to Allah, teachers should advise, care for and pay attention to them. The research findings have a significant impact on the development of moral education strategies for the next generation who not only have academic abilities but are based on the noble principles of the nation and Islamic teachings.